2020
DOI: 10.3390/oceans1040017
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Orientation during the Early Life History of the Pelagic Teleost Mahi-Mahi, Coryphaena hippurus Linnaeus, 1758

Abstract: Understanding the orientation behavior and capabilities in early life history (ELH) of fishes is critical for studying their dispersal but has, surprisingly, never been tested in any pelagic species. We here investigate the ontogeny of orientation and swimming abilities of the pelagic Coryphaena hippurus Linnaeus, 1758 larvae, hereafter mahi-mahi, through their ELH stages using the Drifting In Situ Chamber (DISC) in a laboratory setup. The DISC was deployed in a large (3 m3) circular aquarium in order to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Previous implementation of oriented (e.g., BRW) 22 , 35 38 and unoriented (e.g., CRW) 22 , 32 , 39 movement patterns in biophysical models of larval dispersal, demonstrated a significant effect on dispersal trajectories, settlement success and connectivity patterns 22 , 32 , 35 37 . The mathematical methodology behind such implementation has been extensively described 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous implementation of oriented (e.g., BRW) 22 , 35 38 and unoriented (e.g., CRW) 22 , 32 , 39 movement patterns in biophysical models of larval dispersal, demonstrated a significant effect on dispersal trajectories, settlement success and connectivity patterns 22 , 32 , 35 37 . The mathematical methodology behind such implementation has been extensively described 11 .…”
Section: Discussionmentioning
confidence: 99%
“…As larvae grow, they may prey upon a wider range of zooplankters which could account for the increase in their sRD (Dickmann et al, 2007). Increasing swimming activity and sensory acuity (e.g., orientation behavior) have also been reported to occur from preflexion to postflexion in other fishes including clupeids such as Sardina pilchardus , leading to improved foraging activities for larger larvae which in turn allow them to achieve high growth rates and better nutritional condition (Faillettaz et al, 2020; Grorud‐Colvert & Sponaugle, 2006; Silva et al, 2014; Teodósio et al, 2016). Also, density‐dependent mechanisms such as food limitation are key determinants for growth at high latitudes (Houde, 1989) and are known to affect other sprat nutritional condition (Baumann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies show that most individual larvae swimming in the ocean do so in a directional manner, and there is little ontogenetic improvement in orientation precision [31], however, these were in situ studies limited to postflexion larvae of demersal species. A recent laboratory study on larvae of an oceanic species using both pre-and postflexion larvae showed an ontogenetic increase in orientation precision [81]. Significant directionality among individuals is not as widespread, but even when it is absent, such behaviour can have a meaningful influence on dispersal outcomes [50].…”
Section: Orientationmentioning
confidence: 99%